Assessing Water Quality in the Kelantan River Basin Using WQI: Suspended Solids and Ecosystem Health - Azhar Mohd Zain,; Mohd Shukri Abdul Hamid, (Journal of Science and Technology, 2025)
Water quality in the Kelantan River Basin was assessed in this study using the Water Quality Index (WQI). The Department of Environment Malaysia provided secondary data for this study with seven sampling locations along the Kelantan River Basin. WQI consists of parameters Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxidant Demand (COD), Ammonia Nitrogen (NH3-N), Suspended Solids (SS) and pH. For each sampling station, other WQI parameters did not exceed the threshold value except SS with a medium value of 235.50 mg/L. Krukal Walis test showed that these parameters were found to be significantly different (? < 0.05) between sampling station locations. Based on calculation, the SS sub-index value show 16.7% were classified as clean, 2.4% as slightly polluted and 81.0% as polluted for the entire study period. WQI SS sub-index recorded 46 which are in the Polluted category. Suspended solids are the result of several processes, including river runoff and dredging. Clay is among the inorganic and organic materials that make up it. Excessive levels can bind nutrients and heavy metals, increase water temperature, and degrade water quality. The health of the river basin ecosystem was in Class II water quality determined by the average WQI of 84 at all stations. This study concluded that extensive land development activities in the surrounding areas are affecting water quality, thereby affecting the health of the Kelantan River Basin ecosystem in relation to suspended solids.